Effects of olive pit and almond shell powder on polypropylene - (:unkn) unknown (Trans Tech Publications Ltd, 2017)
The outgrowing ecological and socio-economic awareness, high consumption of petroleum resources and new environmentally strong regulations especially in European countries have prompted researchers to investigate on green materials compatible with the environment. As replacements for conventional synthetic fibers like aramid and glass fibers, natural fibers are increasingly used for reinforcement in thermoplastics due to their low density, good thermal insulation and mechanical properties, reduced tool wear, unlimited availability, low price, and problem-free disposal. The purpose for the addition of cellulose-based fillers to thermoplastics is to reduce the cost per unit volume and to improve stiffness. In the present work I have prepared a series of filled Polypropylene (PP) composites with olive pit and almond shell flour loading (between 0-40 wt %), to study the effect of the filler content on the mechanical and morphological properties of polypropylene polymer composites. © 2017 Trans Tech Publications, Switzerland.
Keywords: Almond shell; Bio composites; Friction; Olive pit; Polypropylene; Wear